Corneal tattooing for esthetic purposes in patients with corneal opacities - Doganay, Derya (Indian J Ophthalmol, 2020)
PURPOSE: This study evaluated corneal tattooing for esthetic purposes in patients with corneal opacification. METHODS: Eight eyes of eight patients were included in the study (four males and four females). Corneal tattooing was achieved by stromal puncture in five patients, femtosecond laser-assisted corneal tattooing in two patients, and femtosecond laser-assisted corneal tattooing and stromal needling (combined procedure) in one patient. In six of the patients, the entire cornea was stained black; in one patient, the center of the cornea (3 mm) was stained black and the periphery was stained dark brown; and in the last patient, the corneal periphery was stained dark brown. Patient satisfaction was evaluated on the first day after surgery and at the last visit as follows: Very satisfied (4), satisfied (3), moderately satisfied (3), and not satisfied (1). RESULTS: The patients ranged in age from 11–80 years. The mean satisfaction score of the patients was 4 and 3.5 on the first postoperative day and at the last visit, respectively. No complication occurred during or after surgery. CONCLUSION: Corneal tattooing for esthetic purposes was successful in both blind eyes and seeing eyes.